PENERAPAN KERUKUNAN ANTAR UMAT BERAGAMA PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG DASAR 1945 - Muhammad Arif Fauzi (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research aims to analyze the application of interreligious harmony based on the perspective of Islamic law and the 1945 Constitution. Religious harmony is an important pillar in maintaining social stability in the midst of Indonesia's diversity. Islamic law emphasizes the value of tolerance and respect, while the 1945 Constitution guarantees freedom of religion as a constitutional right. This research uses a qualitative method with a postpositivism approach, as well as primary and secondary legal sources. Data collection techniques include interviews, documentation, and observation, while data analysis is carried out through reduction, presentation, and conclusion drawn. The results of the study show that social interaction between Muslims and Christians in Sumbersewu Village runs harmoniously through good communication. The principles of maqhâshid al-syarîah, especially hifdzu al-dîn (safeguarding religion), are an important foundation in creating harmony. Factors that support harmony include individual awareness of the importance of living peacefully, strong faith in religion, and mutual respect and tolerance for the implementation of worship in each religion. This research emphasizes that harmony is not only realized through the rule of law, but also through the social awareness of the community